The status and challenges of irrigation infrastructure performance in supporting the agricultural sector: A case study of Kediri Regency, Indonesia - Budi Santoso Eko; Siti Humaira An Nisaa; Fitri Larasati Aida (BIO Web of Conferences)
The increase in population in rural and urban areas has an impact on food availability and security. Agriculture, as a major contributor to food security, faces increasing challenges, such as the decline in the area planted for agricultural commodities, the availability of labor, and the water provision for crops. Climate change will affect water availability, planting patterns, and agricultural production. The government has provided irrigation infrastructure services to increase agricultural production. Limited budget, authority, irrigation water sources, and irrigation service areas have not been able to meet farmers’ needs for irrigation water. This study aims to assess the performance of irrigation infrastructure services based on farmers’ perceptions of these services. Measuring irrigation infrastructure services is based on indicators of physical availability, physical quality, appropriateness, utility, and contribution to the economy. The level of satisfaction with irrigation infrastructure services was measured using a Likert scale. The data are used to compare expected values and perceived values. This measurement obtains service gaps, as mentioned in the IPA (Importance Performance Analysis) method. The respondents to this research are farmers or farmer groups who receive irrigation infrastructure services. The results show significant gaps in several indicators, namely the reliability of the irrigation system, application of irrigation technology, regular irrigation infrastructure checks (O&M), and resilience to climate change.